Comparative Studies on Quality Attributes of Open Sun and Solar Poly-tunnel Dried Wild Pomegranate Arils - Sharma, Anshu; Singh Thakur, Narayan (International Journal of Bio-resource and Stress Management, 2023)
Studies were conducted during the months of September-December in 2011 and January month in 2012 at the Department of Food Science and Technology, Dr. Yashwant Singh Parmar, University of Horticulture and Forestry, Nauni, Solan (HP), to compare the quality attributes of open sun and solar poly-tunnel dried wild pomegranate arils. Quality of open sunand solar poly-tunnel dried wild pomegranate arils was evaluated on the basis of various physico-chemical and sensory quality characteristics. The arils dried in solar poly-tunnel drier possessed higher amount of desirable chemical attributes viz., total solids (90.40%), total soluble solids (39.40 °B), titratable acidity (10.60%), reducing sugars (19.60%), total sugars (23.75%), ascorbic acid (12.70 mg 100 g-1), anthocyanins (28.12 mg 100 g-1) and phenols (108.60 mg 100 g-1). Arils dried in solar poly-tunnel drier had lower amount of undesirable characteristics viz., moisture (9.60%), NEB (0.09 OD), HMF (1.07 ppm) and furfurals (14.40 ppb) as compare to open sun dried arils. The sensory characteristics viz., better colour, taste, texture and overall acceptability scores of arils dried in solar poly-tunnel drier reflected its superiority over open sun. Thus, drying of pre-treated wild pomegranate arils in solar poly-tunnel drier could be a better alternative method to prepare quality dried wild pomegranate arils (anardana) for the upliftment of small industry in the rural areas of developing countries.